Pelatihan Pembuatan Desain Kalender Meja Tahun 2025 dengan Aplikasi Canva - Desipriani Desipriani; Suprianingsih Suprianingsih; Rini Oktari Batubara; Nazwa Nabila Batubara (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This training on making a 2025 desk calendar using the Canva application aims to improve the ability of MAS PAB 2 Helvetia students in making attractive and professional calendar designs. This training uses the Canva application as a graphic design tool that is easy to use and flexible. Participants will learn the basics of graphic design, how to use Canva, and techniques for creating effective calendar designs. It is hoped that the results of this training will improve participants' abilities in creating quality, attractive and efficient calendar designs using the Canva application.